Fetal Bradycardia in Last Trimester Imposed as Fetal Distress: Case Report - Nisa AS; Rahman L; Carolina JS; Pribadi A; Everdien A; Anwar R (International Medical Case Reports Journal)
Aisyah Shofiatun Nisa, Luthfi Rahman, Johanna Sharon Carolina, Adhi Pribadi, Alce Everdien, Ruswana Anwar Department of Obstetrics and Gynecology, Hasan Sadikin General Hospital-Padjadjaran University, Bandung, IndonesiaCorrespondence: Aisyah Shofiatun Nisa, Department of Obstetrics and Gynecology, Hasan Sadikin General Hospital-Padjadjaran University, Pasteur 38, Bandung, Bandung, Indonesia, Tel +6281262142817, Email aisyah23009@mail.unpad.ac.idObjective: Atrioventricular block (AVB) is one of the most common causes of fetal bradyarrhythmia. This case highlights a misdiagnosis of fetal bradyarrhythmia as fetal distress and underscores the importance of accurately distinguishing fetal bradycardia from fetal distress through precise prenatal evaluation.Case Report: A 33-year-old pregnant woman was referred to a tertiary care center after an initial diagnosis of suspected fetal distress at a local hospital. Due to limited resources and qualified clinicians to perform accurate diagnosis, further evaluation at the primary facility was not possible. Upon arrival at the tertiary center, one week later, fetal echocardiography was performed. The fetal heart rate was found to be persistently low at 60– 70 beats per minute. Fetal echocardiography confirmed the presence of congenital heart disease along with a diagnosis of fetal bradyarrhythmia, most likely due to atrioventricular block.Conclusion: Fetal bradycardia may indicate the presence of congenital heart disease or conduction abnormalities such as AV block. Accurate diagnosis using fetal echocardiography is essential to distinguish true bradyarrhythmia from non-specific signs of fetal distress and guide appropriate management.Keywords: case report, congenital heart disease, fetal distress, fetal bradycardia